A Qualitative Study on Lecture Capturing System in Pharmacy Education-Learners’ Perspective - Loganathan, Saranraj; Soundarraj, Rajkumaran; Sujetha, Vishwalingam Murugan (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: The Lecture Capturing System method was implemented in Pharmacy education for a better understanding of the specific content and provides flexibility to review. This study observed pharmacy learners’ perspective on LCS ‘impartus’ usage and its impact on the learning milieu. Materials and Methods: Non-probability (Convenient) sampling design was adopted and a qualitative study was carried out amongst 60 students in their third-year Pharmacy (B.Pharm) students from one of the private pharmacy colleges in Virudhunagar, Tamil Nadu. Structured questions were framed, and data were collected from the respondents. Moreover, descriptive analysis was carried out based on the lecture usage, the impact of LCS on learning and the academic effect of LCS. Results: It showed that learners believed LCS was an effective tool for their understanding and access based on priority and need. However, learners do not have additional time to watch the recorded video. Conclusion: Findings showed that recorded lecture videos are more useful and allow pharmacy learners to engage flexibly in this digital era.
Keywords: Learners; Lecture Capturing System; Pedagogy; Pharmacy education; Qualitative study